N-TUPLE ORBITS TENDING TO INFINITY FOR HILBERT SPACE OPERATORS - Mančevska, Sonja (Matematichki Bilten, 2021)
In [2] we gave some results on the existence of a dense set of vectors each having an n-tuple orbit tending to infinity for sequences of mutually commuting bounded linear operators acting on an infinite-dimensional complex Banach space. In this paper we will show that, in the case of operators on an infinite-dimensional complex Hilbert space, this type of set exists under weaker conditions.